Potassium Currents Activated by Depolarization in Odontoblasts - Kojima, Yuki; Kimura, Maki; Higashikawa, Asuka; Kono, Kyosuke; Ando, Masayuki; Tazaki, Masakzu; Shibukawa, Yoshiyuki (Frontiers in Physiology, 2017)
Increased intracellular free Ca2+ concentrations elicit plasma membrane depolarization, which leads to the activation of K+ currents. However, the precise properties of K+ currents activated by depolarization in odontoblasts remain to be elucidated. The present study identified biophysical and pharmacological characteristics of time-dependent and voltage-activated K+ currents in freshly dissociated rat odontoblasts using patch-clamp recordings in a whole-cell configuration. Using a holding potential of -70 mV, outwardly rectifying time- and voltage-dependent currents were activated by depolarizing voltage. To record pure K+ conductance, we substituted Cl- in both the extracellular and intracellular solutions with gluconate-. Under these conditions, observation of K+ concentration changes in the extracellular solution showed that reversal potentials of tail currents shifted according to the K+ equilibrium potential. The activation kinetics of outward K+ currents were relatively slow and depended on the membrane potential. Kinetics of steady-state inactivation were fitted by a Boltzmann function. The half-maximal inactivation potential was -38 mV. Tetraethylammonium chloride, 4-aminopyridine, and α-dendrotoxin inhibited outward currents in odontoblasts in a concentration-dependent manner, suggesting that rat odontoblasts express the α-subunit of the time- and voltage-dependent K+ channel (Kv) subtypes Kv1.1, 1.2, and/or 1.6. We further examined the effects of Kv activity on mineralization by alizarin Red and von Kossa staining. Continuous application of tetraethylammonium chloride to human odontoblasts grown in a mineralization medium over a 21-day period exhibited a dose-dependent decrease in mineralization efficiency compared to cells without tetraethylammonium chloride. This suggests that odontoblasts functionally express voltage-dependent K+ channels that play important roles in dentin formation.